Outrage [videorecording (DVD)] - Bito Takeshi; Bito Takeshi; Shiina, Kippei, 1964-; Kase, Ryo, 1974-; Kohinata, Fumiyo, 1954- (Magnolia Home Entertainment, 2012)
In a ruthless battle for power, several yakuza clans vie for the favor of their head family in the Japanese underworld. The rival bosses seek to rise through the ranks by scheming and making allegiances sworn over sake. Longtime yakuza Otomo has seen his kind go from elaborate body tattoos and severed fingertips to becoming important players on the stock market.